Correlation and interaction between temperature and freeze-thaw in representative regions of Antarctica. Issue 1 (31st December 2022) - Liang, Dong; Guo, Huadong; Cheng, Qing; Zhang, Lu; Kong, Lingyi
ABSTRACT: As the most sensitive and direct indicator of global climate change, the freezing and thawing of the Antarctic ice sheet is of great significance for research on surface mass and energy balance. In this study, four representative regions in Antarctica were selected and correlation analysis, Granger causality testing, and cluster analysis were applied to comprehensively analyze the correlation and response of spatiotemporal variation in freeze-thaw and temperature. The conclusions are as follows. (1) In the Antarctic Peninsula, a phenomenon was demonstrated that the summer shifts rearward. Hotter December and colder March temperatures were observed in the Amery Ice Shelf and Queen Maud Land. (2) The Antarctic Peninsula featured the most severe degree of melting among the four regions, with the largest melt area in the past 30 years appearing during the 2015/2016 season. However, the number of melt days in most areas of the Antarctic Peninsula was observed to have decreased. (3) There is a strong correlation between the freeze-thaw state of the Antarctic ice sheet and temperature, as well as spatial differences among regions, but the data were clustered at different time scales.